“Der kom et Hølæs kørende...”: Tilsynekomstens æstetik i Johannes V. Jensens Kongens Fald - Ehlers Dam, Anders (Passage - Tidsskrift for litteratur og kritik, 2022)
This article offers a reading of Johannes V. Jensen’s novel The Fall of the King under the perspective of an aesthetics of appearing. Firstly, it presents recent theories of appearing (Seel, Gumbrecht, Bohrer). Secondly, it analyzes selected passages of the novel, where different kinds of appearing are described. In its final part, the article discusses appearing in relation to aesthetic intensity.